IMPACT OF INFECTION BY H. PYLORI ON GASTRIC PARIETAL CELL PHYSIOLOGY: REVIEW - Bakheet NZ, Noor Zuhair (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This review aims to highlight the strategies used by Helicobacter pylori to influence the physiology of gastric parietal cells, affecting gastric acid secretion, epithelial elasticity, and the development of various gastric diseases. Method: The study reviews existing literature on Helicobacter pylori infection and its impact on gastric parietal cells, including mechanisms of colonization, inflammatory response, and physiological effects on the stomach and duodenum. Results: Helicobacter pylori infection can significantly affect parietal cells, which are essential for gastric acid production. Upon Helicobacter pylori infection, inflammatory cells replace normal glandular cells, leading to hypo- or hyperchloremia, based on the colonization site in the stomach. Chronic colonization of the gastric lumen promotes hyperacidity and duodenal ulcers, while hypoacidity resulting from long-term Helicobacter pylori infection of the gastric corpuscle and fundus increases the risk of gastric cancer and may damage these cells, gastric atrophy, and other complications. Novelty: In summary, Helicobacter pylori infection has a complex and multifaceted effect on the physiology of gastric parietal cells, affecting acid secretion, epithelial cell elasticity, and the development of various gastric diseases.